Dietary Carotenoids in Managing Metabolic Syndrome and Role of PPARs in the Process - Purohith, Raghunandan; Nagalingaswamy, Nagendra P.M.; Shivananju, Nanjunda S. (Current Nutrition & Food Science, 2020)
Metabolic syndrome is a collective term that denotes disorder in metabolism, symptoms of which include hyperglycemia, hyperlipidemia, hypertension, and endothelial dysfunction. Diet is a major predisposing factor in the development of metabolic syndrome, and dietary intervention is necessary for both prevention and management. The bioactive constituents of food play a key role in this process. Micronutrients such as vitamins, carotenoids, amino acids, flavonoids, minerals, and aromatic pigment molecules found in fruits, vegetables, spices, and condiments are known to have beneficial effects in preventing and managing metabolic syndrome. There exists a well-established relationship between oxidative stress and major pathological conditions such as inflammation, metabolic syndrome, and cancer. Consequently, dietary antioxidants are implicated in the remediation of these complications. The mechanism of action and targets of dietary antioxidants as well as their effects on related pathways are being extensively studied and elucidated in recent times. This review attempts a comprehensive study of the role of dietary carotenoids in alleviating metabolic syndromewith an emphasis on molecular mechanism-in the light of recent advances.
Keywords: oxidative stress